More support for hydrogen export than its domestic application in Australia - Bharadwaj, B.; Weder, F.; Ashworth, Peta (2023)
Early research has suggested the societal acceptance of hydrogen to decarbonise our energy supply is relatively high. However, the specific aspects of hydrogen that citizens support remain unknown. To investigate public support for export and domestic applications of hydrogen, this study implemented an Australian nationally representative survey. Using a quasi-experimental design, information was provided to respondents as an intervention to test individual responses. The information included a short video, followed by images and text descriptions. The study found the combined information package increased societal support by 10% when compared to the baseline with the change in support for export applications being significantly higher compared to domestic applications. While encouraging the development of Australia’s export industry it was also found that respondents’ general support depends on their socio-economic characteristics and geographic location.